Analisis Literasi Ekonomi Digital dalam Upaya Menurunkan Tingkat Kemiskinan di Indonesia - Tanjung, Anisa; Rangkuty, Dewi Mahrani (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2024)
Poverty often serves as an indicator of a country or region's developmental progress. The digital economy is seen as a means to enhance economic self-reliance and national resilience, thereby boosting national competitiveness and fostering economic growth to alleviate poverty. Utilizing time series data from 2008 to 2022 and employing a simultaneous Two-Stage Least Square (TSLS) approach, research findings reveal a bidirectional relationship between poverty and economic growth. The study demonstrates that the E-money variable significantly influences economic growth and, conversely, has a significant impact on poverty rates. This underscores the significance of economic policies aimed at fostering economic growth to combat poverty.